Sufi Healing in Martin Lings View: Dzikir and Prayer as Healing Therapy - Endrika Widdia Putri; Efendi . (Program Studi Tasawuf dan Psikoterapi, 2022)
The problem of spiritual emptiness is not enough to only be cured by medical methods, but also by spiritual treatment, for example by Sufi healing methods. Sufi healing methods are considered relevant to heal patients who experience emotional and mental disorders. This paper focuses on studying Sufi healing with the method of prayer and dzikir in the view of Martin Lings. This paper is analyzed with a qualitative approach using exploratory and analytical methods. The findings obtained are, for Martin Lings the conception of Sufism can be used as a method for spiritual treatment, where the goal is to lead people who have problems with their spiritual emptiness to have kindness and peace of mind. Healing therapy methods that can be used are prayer and dzikir. According to Martin Lings, prayer will give birth to a sense of awareness of the human need for God. Meanwhile, with dzikir gives birth to self-realization of all the shortcomings of oneself and the hope of Allah's forgiveness.